2018
DOI: 10.7213/1981-4178.2018.161101
|View full text |Cite
|
Sign up to set email alerts
|

Panorama brasileiro do bem-estar de suínos

Abstract: A suinocultura industrial brasileira é representativa em nível mundial, detendo uma produção de qualidade reconhecida e competitiva, na qual a classifica como quarta maior exportadora, contribuindo expressivamente com o PIB do país. Por sua vez, o tema bem-estar animal (BEA), que já se encontra bem estabelecido em importantes países produtores de suínos, vem ganhando notoriedade nesta cadeia, com consumidores, investidores e empresas alimentícias pressionando a indústria brasileira para incrementar estas práti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
(29 reference statements)
0
10
0
9
Order By: Relevance
“…To evaluate the welfare parameters the indicators of the Welfare Quality® (2009) protocol were considered and adapted, with the parameters related exclusively to the pregnancy phase (Table 1). Each indicator was scored with "0" attributed to the observations in which well-being was considered good or "1" well-being was compromised or severely compromised (Dias et al, 2018), except for the body condition score indicator that was only observed individually in a 1 to 5 scale. The females of both groups (PEN1 and PEN32) were visually and individually observed during 40 to 60 seconds at two different times throughout the experiment, before 35 days of pregnancy (between 7 and 20 days) and after 35 days of pregnancy (between 42 and 65 days), when all the females were group-housed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the welfare parameters the indicators of the Welfare Quality® (2009) protocol were considered and adapted, with the parameters related exclusively to the pregnancy phase (Table 1). Each indicator was scored with "0" attributed to the observations in which well-being was considered good or "1" well-being was compromised or severely compromised (Dias et al, 2018), except for the body condition score indicator that was only observed individually in a 1 to 5 scale. The females of both groups (PEN1 and PEN32) were visually and individually observed during 40 to 60 seconds at two different times throughout the experiment, before 35 days of pregnancy (between 7 and 20 days) and after 35 days of pregnancy (between 42 and 65 days), when all the females were group-housed.…”
Section: Methodsmentioning
confidence: 99%
“…The European Union (EU) has been a pioneer in the development of many measures to improve animal welfare in the production system, and since 2013 it has become mandatory to abolish individual pen for sows and gilts after 28 days of pregnancy and obligated to use group-housed after this period (Knox et al, 2014;Dias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O aumento da preocupação da sociedade com a forma como os alimentos são produzidos tem promovido debates e gerado uma inquietação no sentido de que os sistemas de produção contemplem cada vez mais condutas voltadas para o bem-estar animal (BEA) (DIAS et al, 2018). Em 2016, em pesquisa realizada no Brasil, 91% dos brasileiros consultados declararam que animais criados sob adequado bem-estar produzem uma carne de melhor qualidade (WORLD ANIMAL PROTECTION, 2016).…”
Section: Considerações Sobre Bem-estar Em Suínosunclassified
“…On the other hand, housing in collective pens, when properly implemented and managed, allows for greater positive social contact and reduces stress, while maintaining similar zootechnical performance (C. P. Dias & Calvo, 2016). The results obtained indicate that Brazil, even without official regulations on the subject of animal welfare, is heading towards a possible ban on continuous accommodation in gestation crates (C. P. Dias, Silva, Foppa, Callegari, & Pierozan, 2018). 1 Farms with pens with 100% compact floor but also with pens with compact/slatted floor.…”
mentioning
confidence: 95%